Compensation, Stress, And Retention: Crafting A Satisfied Workforce In Guarantee Companies - Indra Budi Setiyawan; Muhammad Leonard Gustav Qhadafi; Syafira Kamilatul Hidayat; Abdul Rohman (Eduvest - Journal of Universal Studies, 2024)
This study examines the effects of compensation and work-related stress on employee retention, with job satisfaction acting as a mediating factor within Indonesia's guarantee company sector. A quantitative approach was used, involving 216 permanent employees from guarantee companies who had been employed for at least one year. Data was gathered through an online survey using a 5-point Likert scale, and analysis was conducted with SMART PLS. The findings reveal that compensation has a positive impact on job satisfaction, while work stress negatively affects it. Additionally, job satisfaction significantly boosts employee retention. Interestingly, the direct influence of compensation and work stress on employee retention was not statistically significant. However, job satisfaction strongly mediates the relationship between compensation and employee retention (suggesting a positive mediation) as well as the relationship between work stress and employee retention (indicating a negative mediation). These results provide valuable insights into the factors affecting employee retention in the guarantee industry and offer practical suggestions for organizations aiming to improve their retention strategies. This research uniquely integrates compensation, work stress, job satisfaction, and employee retention into one framework, particularly within the less-explored context of the guarantee sector